Enhanced lipid metabolism confers the immunosuppressive tumor microenvironment in CD5-positive non-MYC/BCL2 double expressor lymphoma - Liu, Meng-Ke; Cheng, Li-Li; Yi, Hong-Mei; He, Yang; Li, Xiao; Fu, Di; Dai, Yu-Ting; Fang, Hai; Cheng, Shu; Xu, Peng-Peng; Qian, Ying; Feng, Yan; et al. (Frontiers in Oncology, 2022)
Lymphoma cells expressing CD5 (CD5+) confers inferior outcome of diffuse large B-cell lymphoma (DLBCL), especially in non-MYC/BCL2 double expressor (non-DE) patients. In tumor microenvironment, CD5+ non-DE tumor revealed increased proportion of immunosuppressive M2 macrophages, enhanced pathways related to macrophage activation and migration. In accordance to M2 activation, lipid metabolism was upregulated, including fatty acid uptake and fatty acid oxidation, which supplied energy for M2 macrophages polarization and activation. Meanwhile, CD36 expression was upregulated and strongly correlated to proportion of M2 macrophages in CD5+ non-DE DLBCL. In vitro, DLBCL cell line (LY10) overexpressing CD5 significantly increased M2 proportion in comparison with control when cocultured with peripheral blood mononuclear cells. Addition of metformin significantly decreased M2 proportion and CD36 expression level in the coculture systems, indicating that metformin could target altered lipid metabolism and decrease M2 macrophages in DLBCL, especially in CD5+ non-DE lymphoma. In conclusion, enhanced lipid metabolism and M2 macrophage activation contributed to the immunosuppressive tumor microenvironment and could be potential therapeutic targets in CD5+ non-DE DLBCL.